2007
DOI: 10.1099/vir.0.82906-0
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of overlapping polymerase and surface protein genes of hepatitis B virus

Abstract: The genome of hepatitis B virus (HBV) provides a striking example of gene overlapping. In particular, the surface protein gene S is overlapped completely by the polymerase gene P. Evolutionary constraints in overlapping genes have been demonstrated for many viruses, with one of the two overlapping genes being subjected to positive selection (adaptive evolution), while the other one is subjected to purifying selection. Yet, for HBV to persist successfully, adaptive evolution of both the P and S genes is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…For monopartite begomoviruses, C4 is a pathogenicity determinant that is involved in movement and suppression of host defense responses, whereas the homologues of C4 encoded by most NW begomoviruses do not play a role in pathogenicity. This strategy, which allows viruses to condense a maximal amount of information into short genomes, has been widely used by a number of animal and plant-infecting viruses (Zaaijer et al, 2007). Given the rapid spread of TYLCV in China, it will be interesting to monitor the evolutionary constraints in vivo in experimentally infected tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…For monopartite begomoviruses, C4 is a pathogenicity determinant that is involved in movement and suppression of host defense responses, whereas the homologues of C4 encoded by most NW begomoviruses do not play a role in pathogenicity. This strategy, which allows viruses to condense a maximal amount of information into short genomes, has been widely used by a number of animal and plant-infecting viruses (Zaaijer et al, 2007). Given the rapid spread of TYLCV in China, it will be interesting to monitor the evolutionary constraints in vivo in experimentally infected tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the codon usage, the relative positions of the codons have been proposed to be important. Zaaijer et al (54) have shown that the overlapping surface and polymerase genes of HBV evolve independently. They showed that most of the replacement mutations occur in P1/S3 (the nucleotide in the first position in polymerase codons and in the third position in surface codons) and P3/S2, while P2/S1 mutations are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of synonymous and nonsynonymous mutations were analyzed with the SNAP program (www.hiv.lanl.gov) (43). The hypothesis of independent evolution in overlapping genes was tested as described by Zaaijer et al (44). Variation was assessed by determining the entropy values for individual amino acids and nucleotides by using the BioEdit software (45).…”
Section: Methodsmentioning
confidence: 99%
“…This explains how convergent evolution in AC4 genes of NW bipartite begomoviruses can generate AC4/C4 proteins with functional similarity to C4 counterparts in OW monopartite begomoviruses while maintaining the more conserved Rep protein sequence. This strategy, which allows for maximizing the viral genome size and maintaining differential rates of mutation in overlapping genes, is used by a range of animal and plant-infecting viruses (44).…”
Section: Tolcd In Ecuador Andmentioning
confidence: 99%